Reinterpretation Of Political Islamic Movement In Indonesia Within The Social Ethics Perspective Of Abid Al-Jabiri - Farid, Mohtazul; Efendi, Erfan (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
Radical Islam, as the basis of political movements, has been widely studied by scholars and political observers. The existing study efforts have produced many findings based on the perspectives and approaches used from an economic, social, cultural, to theological point of view. However, there still needs to be an Islamic ethical perspective to examine the model of the Islamic political movement. This article examines the thoughts of Abid Al-Jabiri regarding the concept of social ethics from a new point of view. This library research describes Al-Jabiri's ethical thinking based on his works. The results of this study indicate 1) The roots of the emergence of the political Islam movement departed from a literalist understanding of Islamic teachings so that the political goal to establish an Islamic state in Indonesia was born from a misinterpretation of Islamic teachings 2) The contours of the movement were identity politics born of the dichotomous paradigm 3) and the consequences This movement contradicts Al-Jabiri's Islamic ethical thought which emphasizes the public benefit and goodness because the acts of terror carried out have no implications for the benefit of the Indonesian people.